2009
DOI: 10.1089/thy.2008.0244
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Lymph Node Metastasis in Papillary Thyroid Carcinoma: Results of Therapeutic Lymph Node Dissection

Abstract: Skip metastases occur in a minority of patients with PTMC. We recommend, therefore, that preoperative studies in patients suspected of having PTMC focus not only on nodes in the central compartment but also lateral cervical nodes since the information obtained would guide the extent of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
118
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(133 citation statements)
references
References 35 publications
9
118
6
Order By: Relevance
“…Extrathyroidal invasion (16), multifocality (17) and bilateral thyroid tumors of PTMC (18) are the important risk factors in lymph node metastasis that represent biological characteristics of progress. Although the study by McCarthy et al (19) reported that multifocality is highly homologous within the gland and is not associated with tumor invasion, Shindo et al (17) and Chow et al (20) found that neck lymph node metastasis and tumor multifocality remain significantly correlated, which is the major reason for lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Extrathyroidal invasion (16), multifocality (17) and bilateral thyroid tumors of PTMC (18) are the important risk factors in lymph node metastasis that represent biological characteristics of progress. Although the study by McCarthy et al (19) reported that multifocality is highly homologous within the gland and is not associated with tumor invasion, Shindo et al (17) and Chow et al (20) found that neck lymph node metastasis and tumor multifocality remain significantly correlated, which is the major reason for lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node metastases are regarded as prognostic factor of PTC patient's survival. There are some reports demonstrating higher frequency of nodal involvement in younger patients, whereas other point out the nodal involvement and patient's age $45 as factors affecting survival in patients with papillary thyroid carcinoma [40,41]. We found that PDPN neoexpression is strongly correlated with older ($45) patients age, which is one of the several classical clinico-pathological highrisk factors in papillary thyroid carcinomas.…”
Section: Discussionmentioning
confidence: 46%
“…Mercante et al [2009], in their large study of 445 cases demonstrated that age was not a significant risk factor for neck recurrence or distant metastasis. Another study reported that patients with lymph node metastasis were younger than those without lymph node metastases [Chung et al, 2009]. Y.…”
Section: Age In Ptmcmentioning
confidence: 99%
“…PTMCs also showed a high incidence of regional lymph node metastasis, occurring in 12--64% of patients [Besic et al, 2008;Choi et al, 2008;Chung et al, 2009;J. Lee et al, 2006;Y.…”
Section: Ptmc In the Staging Systemsmentioning
confidence: 99%